ACQUIRED HYPOALDOSTERONISM WITH RENAL TUBULAR ACIDOSIS TYPE 4 IN A DIABETIC PATIENT - Seong, Calvin Ooi Gim; Mugilarasan, Sivasangkari (Journal of the ASEAN Federation of Endocrine Societies, 2023)
INTRODUCTION/BACKGROUND Renal tubular acidosis (RTA) type 4 is an uncommon cause of hyperkalaemia with non-anion gap acidosis. Here we present a case of acquired hypoaldosteronism. CASE A 60-year-old female with poorly controlled diabetes (HbA1c 9.3%) and hypertension presented with a twoyear history of multiple episodes of asymptomatic hyperkalaemia. She was not on RAAS blockade or drugs causing hypoaldosteronism. There was no family history of RTA. Physical examination was unremarkable. Laboratory investigations revealed hyperkalaemia (5.9 mmol/L), normal sodium (136 mmol/L), metabolic acidosis (pH 7.27; HCO3 17.8) and impaired renal function (creatinine 118 mmol/L; eGFR 43 ml/min/1.73m2). Serum cortisol was normal (517.7 nmol/L) and serum aldosterone was low (<103 pmol/L), with serum renin mildly elevated (125.60 mU/L; supine 4.2-59.7; upright 5.399.1). There was no sonographic evidence of any suprarenal mass. She was commenced on frusemide 20 mg daily. However, due to persistent hyperkalaemia, fludrocortisone 50 mcg daily was added. RTA type 4 results from aldosterone deficiency or resistance and is associated with diabetes in 50% of cases. Hypoaldosteronism can be due to reduced stimulus to release (hyporeninaemic) or reduced synthesis or secretion (drugs like heparin, NSAIDs, ciclosporin; congenital adrenal hypoplasia); whereas aldosterone resistance can develop in target organs (pseudohypoaldosteronism) due to tubulointerstitial disease or diabetic nephropathy. Chronic hyperglycaemia can lead to diabetic and autonomic nephropathy resulting in juxtaglomerular apparatus injury or deficiency in the conversion of prorenin to active renin. However, renin levels were unexpectedly normal in our patient. Initial treatment includes a lowpotassium diet, diuretics, ion-exchange resins, and in persistent cases, fludrocortisone. CONCLUSION Acquired hypoaldosteronism should be considered in the diabetic patient with mild non-anion gap metabolic acidosis and hyperkalemia, especially if disproportionate to the degree of renal impairment.